**After having studied what** **algebraic expressions**** and** **equivalent algebraic expressions**** are, the next thing to do is to understand how to collect like terms.**

Since the numbers and variables are not similar (or, 'like') terms, they cannot be simplified into a single group and, therefore, we have to write them separately ($X,Y$).

**Example with Two Variables**

The expression $4+2+2X+3X+Y+2Y=$ can be simplified as follows:

$5X+3Y+6$

## Practice Exercises: Collecting Like Terms

Combine like terms in order to obtain shorter expressions:

- $X+X=$
- $5+8-9+5X-4X=$
- $5+0+8X-5=$
- $11+5X-2X+8=$
- $13X+5-4.5X+7.5X=$

Collect like terms to obtain shorter expressions. Then, using what we have learned about the numerical value of algebraic expressions, apply $X=5$ and solve.

- $2X+5X\cdot4=$
- $2.3X+0.4X-0.7X=$
- ${X\over15}+{X\over15}=$
- ${3\over8}X-{2\over8}X+5=$
- $(7+Y):3=$

**If you are interested in this article, you may also like the following articles:**

**On** **Tutorela**** website,** **you can find a wide range of useful articles about mathematics!**

Join Over 30,000 Students Excelling in Math!

Endless Practice, Expert Guidance - Elevate Your Math Skills Today

## Exercises: Collecting Like Terms

### Exercise 1

**Task:**

$3\frac{b}{a}\cdot1\frac{3}{8}a+\frac{5}{8}b+\frac{4}{18}m+\frac{9}{10}a+\frac{2}{3}m=\text{?}$

**Solution:**

Enter the corresponding elements.

$3\frac{b}{a}\times1\frac{3}{8}a+\frac{5}{8}b+\frac{9}{10}a+\frac{4}{18}m+\frac{2}{3}m=$

Convert the mixed fractions into improper fractions.

$3\frac{b}{a}\times\frac{(8+3)}{8}a+\frac{5}{8}b+\frac{9}{10}a+\frac{4}{18}m+\frac{2}{3}m=$

Solve accordingly.

$\frac{3\times11\times b\times a}{8\times a}+\frac{5}{8}b+\frac{9}{10}a+\frac{4+2\times6}{18}m=$

Simplify to $a$ in the equation.

$\frac{33}{8}b+\frac{5}{8}b+\frac{9}{10}a+\frac{16}{18}m=$

$\frac{33+5}{8}b+\frac{9}{10}a+\frac{8}{9}m=$

$\frac{38}{8}b+\frac{9}{10}a+\frac{8}{9}m=$

$4\frac{3}{4}b+\frac{9}{10}a+\frac{8}{9}m=$

**Answer:**

$4\frac{3}{4}b+\frac{9}{10}a+\frac{8}{9}m=$

### Exercise 2

**Task:**

$\frac{3}{8}a+\frac{14}{9}b+1\frac{1}{9}b+\frac{6}{8}a=\text{?}$

**Solution:**

First, group the terms together:

$\frac{3}{8}a+\frac{6}{8}a+\frac{14}{9}b+1\frac{1}{9}b$

Then reduce in correspondence and convert the mixed fractions into improper fractions.

$\frac{3+6}{8}a+\frac{10}{9}b+\frac{14}{9}b=$

$\frac{9}{8}a+\frac{10+14}{9}b=$

$1\frac{1}{8}a+\frac{24}{9}b=$

$1\frac{1}{8}a+2\frac{6}{9}b=$

$1\frac{1}{8}a+2\frac{2}{3}b$

**Answer:**

$1\frac{1}{8}a+2\frac{2}{3}b$

Do you know what the answer is?

### Exercise 3

$7.3\times4a+2.3+8a=?$

**Solution:**

We start with the multiplication operation.

$(7.3\times4a)+2.3+8a=$

$(29.2a)+2.3+8a=$

Then we add together as much as we can and rewrite the equation to make it clearer:

$29.2a+8a+2.3=$

$37.2a+2.3=$

**Answer:**

$37.2a+2.3$

### Exercise 4

**Task:**

Solve the following equation:

$a+b+bc+9a+10b+3c=\text{?}$

**Solution:**

The terms are substituted into the expression according to the order: $a, b, c$.

$a+9a+b+bc+10b+3c=$

We continue with the addition operations.

$10a+11b+bc+3c=$

The terms containing $c$ are converted for the equation since they cannot be simplified further.

$10a+11b+(b+3)c$

**Answer:**

$10a+11b+(b+3)c$

### Exercise 5

**Task:**

**Solve the following equation:**

$3z+19z-4z=\text{?}$

**Solution:**

We start with the addition operation:

$22z-4z=$

We continue solving accordingly.

$18z$

**Answer:**

$18z$

## Review Questions

**What are like terms?**

Like terms in an algebraic expression are those that have the same variable with the same exponent, regardless of the sign and the coefficientβthat is, the sign and the coefficient can be different, but the variable and the exponent must be the same. For example:

$3x^2$ y $-11x^2$

$8a^5$ y $8a^5$

$-7m$ y $\frac{2}{3}m$

**How do you simplify expressions?**

In order to simplify algebraic expressions, we need to work out if there are any like terms and then group them together before performing the operations (addition, subtraction, etc.).

**Example 1**

**Task:** Simplify the following expression:

$3x^2-7x+6-5x^2-x-1$

**Solution:**

First we need to group the like terms and then perform the operations.

$3x^2-5x^2-7x-x+6-1$

$-2x^2-8x+5$

**Answer:**

$-2x^2-8x+5$

**Example 2**

**Task:** Simplify the following expression:

$8m^2+2m+7=3m^3+5m^2+2m-5$

**Solution:**

In this case we need to put all the terms on one side and combine the like terms:

$-3m^3+8m^2-5m^2+2m-2m+7+5=$

$-3m^3+3m^2+12=$

**Answer:**

$-3m^3+3m^2+12=$

**How do you simplify a function?**

In order to simplify a function, we must also work out if there are any like terms and group them together in order to simplify them.

**Example**

**Question:** Simplify the following function:

$f\left(a\right)=-5a^2+2a-4+2a^2+5a$

**Solution:**

In this function we can see that there are like terms, so we can group them to simplify them.

$f\left(a\right)=-5a^2+2a^2+2a+5a-4$

$f\left(a\right)=-3a^2+7a-4$

**Answer:**

$f\left(a\right)=-3a^2+7a-4$

Do you think you will be able to solve it?

## Examples with solutions for Simplifying Expressions (Collecting Like Terms)

### Exercise #1

### Video Solution

### Step-by-Step Solution

To solve the exercise, we will reorder the numbers using the substitution property.

$18x-8x+4x-7-9=$

To continue, let's remember an important rule:

1. It is impossible to add or subtract numbers with variables.

That is, we cannot subtract 7 from 8X, for example...

We solve according to the order of arithmetic operations, from left to right:

$18x-8x=10x$$10x+4x=14x$$-7-9=-16$Remember, these two numbers cannot be added or subtracted, so the result is:

$14x-16$

### Answer

### Exercise #2

$7.3\cdot4a+2.3+8a=\text{?}$

### Video Solution

### Step-by-Step Solution

It is important to remember that when we have numbers and variables, it is impossible to add or subtract them from each other.

We group the elements:

$7.3Γ4a + 2.3 + 8a =$

29.2a + 2.3 + 8a =

$37.2a + 2.3$

And in this exercise, this is the solution!

You can continue looking for the value of a.

But in this case, there is no need.

### Answer

### Exercise #3

$\frac{9m}{3m^2}\times\frac{3m}{6}=$

### Video Solution

### Step-by-Step Solution

According to the laws of multiplication, we must first simplify everything into one exercise:

$\frac{9m\times3m}{3m^2\times6}=$

We will simplify and get:

$\frac{9m^2}{m^2\times6}=$

We will simplify and get:

$\frac{9}{6}=$

We will factor the expression into a multiplication:

$\frac{3\times3}{3\times2}=$

We will simplify and get:

$\frac{3}{2}=1.5$

### Answer

### Exercise #4

### Video Solution

### Answer

### Exercise #5

### Video Solution

### Answer